Aposematic signals in North American black widows are more conspicuous to predators than to prey. (27th February 2016) - Brandley, Nicholas; Johnson, Matthew; Johnsen, Sönke
Lay Summary: Dangerous prey often use bright colors to warn off potential predators, but should they be obvious to everything? Black widows suggest not. Both the color and patterning of adult female black widows suggests that their appearance is more conspicuous to their predators (birds) than their prey (insects). We suggest that the characteristics of warning signals may not evolve solely to warn off predators, but also need to account for other animals that may view the signal. Abstract: The iconic red hourglass of the black widow spiders (genus Latrodectus ) is traditionally considered an aposematic signal, yet experimental evidence is lacking. Here, we present data that suggest that black widow coloration may have evolved to be an aposematic signal that is more conspicuous to their vertebrate predators than to their insect prey. In choice experiments with wild birds, we found that the red-and-black coloration deters potential predators: Wild birds were 3 times less likely to attack a black widow model with an hourglass than one without. Using visual-system appropriate models, we also found that a black widow's red-and-black color combo is more apparent to a typical bird than a typical insect. Additionally, an ancestral reconstruction reveals that red dorsal coloration is ancestral in black widows and that at some point some North American widows lost their red dorsal coloration. Behaviorally, differences in red dorsal coloration between 2 North American species are accompanied by differences in microhabitat that affects how often a bird will view a black widow's dorsal region. All observations are consistent with a cost–benefit trade-off of being more conspicuous to predators than to prey. We suggest that limiting detection by prey may help explain why red and black aposematic signals occur frequently in nature.